Mobile Video Annotations - A Case Study on Supporting Rehabilitation Exercises - Cunha, Bruna C. R.; Correia, Rodolfo Dias; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
Annotations enable us to highlight key points or add information to content presented, for instance, on paper or digital media. Even though smartphones and tablets facilitate video capturing, currently only few applications allow limited video annotations using the mobile device itself. Given that video annotations can assist many tasks that depend or can be enhanced by video capturing, in previous work we have contributed with a tool for allowing multimodal video annotation using mobile devices. Upon experimenting with the tool, we identified that reviewing rehabilitation exercise videos can be especially enhanced with video annotations. Professionals in the field of physiotherapy and occupational therapy can add relevant annotations for their patients to improve performance of their exercises. After an evaluation with a specialist in occupational therapy, we identified new requirements associated with the monitoring of patients. We then identified the opportunity to develop a monitoring system with the collaboration of two rehabilitation specialists. Since these two specialists work with mirror therapy, we defined requirements that are relevant for this type of therapy. The system was developed to support the monitoring of exercises combined with video recording and annotation capabilities. The system aims to support rehabilitation therapy by distance: therapists can monitor patients as they record videos that are sent for evaluation. We identified requirements that may be applied in many scenarios, however mirror therapy demanded many specific requirements related to the recording of videos.